2018
DOI: 10.1091/mbc.e17-08-0535
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced lipolysis results in lipotoxicity and mitochondrial damage in peroxisome-deficient Pex19 mutants

Abstract: Peroxisomal dysfunction is often associated with mitochondrial abnormalities for unknown reasons. We found that peroxisomal loss upon Pex19 mutation in Drosophila results in Hnf4 hyperactivation with free fatty acid accumulation and mitochondrial damage as a consequence. Genetic reduction of Hnf4 in Pex19 mutants improves all phenotypes, including lethality.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 47 publications
4
49
3
Order By: Relevance
“…We found that the loss of peroxisomes induced the fragmentation of mitochondria, whereas some previous studies showed that the loss of peroxisomes promoted the enlargement of mitochondria (Bülow et al, 2018; Rahim et al, 2016). This difference may be attributable to the long-term ablation of peroxins in these previous studies, which likely resulted in secondary effects due to the accumulation of ROS and subsequent cellular damage.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…We found that the loss of peroxisomes induced the fragmentation of mitochondria, whereas some previous studies showed that the loss of peroxisomes promoted the enlargement of mitochondria (Bülow et al, 2018; Rahim et al, 2016). This difference may be attributable to the long-term ablation of peroxins in these previous studies, which likely resulted in secondary effects due to the accumulation of ROS and subsequent cellular damage.…”
Section: Discussioncontrasting
confidence: 75%
“…We next addressed the mechanism by which the diffusion of cytochrome c is increased in peroxisome-deficient MEFs. Although previous studies have shown that long-term deletion of Pex genes results in ROS accumulation (Bülow et al 2018, Rahim et al 2016), the cytosolic ROS level of our Pex3-deficient MEFs as measured with CellROX did not appear to differ from that of control MEFs (Fig. 6,A and B).…”
Section: Resultscontrasting
confidence: 54%
See 1 more Smart Citation
“…A recent study employing Drosophila melanogaster and human fibroblasts has linked mitochondrial dysfunctionality in PEX19 deletion cells with a detrimental cycle of transcriptionally activated constant fatty acid synthesis and mitochondrial β‐oxidation . Although this study suggests an interesting link between peroxisomes/lipid droplets and mitochondria, a similar conclusion cannot be drawn for yeast cells because they do not possess a homologous transcriptional regulation mechanism, which can be responsible for the vicious cycle, and yeast mitochondria do not perform β‐oxidation.…”
Section: Discussionmentioning
confidence: 59%
“…On the one hand, they generate H 2 O 2 as a consequence of fatty acid peroxidation; on the other hand, they contain a set of antioxidant enzymes and function therefore as reactive oxygen species (ROS) scavenging organelles [80]. Interestingly, loss of Pex19 in D. melanogaster causes ROS accumulation and mitochondrial damage, and a mouse model of Zellweger syndrome displays a similar phenotype [81,82]. Elevated endogenous ROS are known to induce genome instability [83,84].…”
Section: Discussionmentioning
confidence: 99%